PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN SABILURROSYAD GASEK MALANG - Salimatul Wadimah; M. Ilyas Thohari; Moh. Muslim (VICRATINA, 2020)
In the process of character building is not enough with formal education only, but also need to be supported and cooperate with institutions outside the formal school, such as Pesantren. Pondok Pesantren is known as the oldest educational institution. Pondok Pesantren is also known with the characteristic in shaping the character of students into students who have the character Akhlakul Karimah. The same is also sought by Pondok Pesantren Sabilurrosyad Gasek Malang in shaping the character of students. This research was conducted to know the character of the planned, the process of character building students, and the results of the establishment of students at Pondok Pesantren Sabilurrosyad Gasek Malang. This research uses qualitative descriptive approaches using several data collection processes including observations, interviews, and documentation. Furthermore, researchers use qualitative analysis to study the results of research, data reduction, data display, and draw conclusions. The results of the research that has been done are students have discipline, religious, Tawadhu ', and nationalists using a variety of methods such as habituation, reward and punishment, discourse and motivation and supported by activities in boarding schools.Kata Kunci: Pembentukan Karakter, Santri, Pondok Pesantren